Comparison between ActiGraph GT3X and ActivPAL to assess sedentary behavior during the school period - Luciana Leite Silva Barboza; André Oliveira Werneck; David Ohara; Enio Ricardo Vaz Ronque; Marcelo Romanzini; Danilo Rodrigues Pereira da Silva (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aims: This study aimed to compare the sedentary time measured using the ActiGraph GT3X accelerometer with the measurement of sitting and standing time obtained by ActivPAL inclinometers. Methods: This was a cross-sectional study conducted with a sample of 60 schoolchildren (34 males) of one elementary public school in Brazil. The students used both an ActiGraph GT3X accelerometer and an ActivPAL inclinometer, concurrently, positioned at the beginning and removed at the end of the school shift, for four days. For analysis, paired Student's t-tests, Pearson's correlation coefficients, intraclass correlation coefficients, and Bland-Altman plots were used. Results: When comparing sedentary time with sitting time, although correlated (r = 0.53; p < 0.001), the mean minutes were different (134.2 min/day in ActiGraph GT3X vs 120.3 min/day in ActivPAL; p < 0.001), with a bias of 13.9 min/day. When comparing the measurement of sedentary time with the sum of the sitting time plus standing time, different mean minutes were also observed (134.2 min/day in ActiGraph GT3X vs 177.0 min/day in ActivPAL; p < 0.001), and although the correlation was stronger (r = 0.75; p < 0.001), the bias was higher (−42.8 min/day). Conclusion: Sedentary time derived from the ActiGraph GT3X device should be used with caution to evaluate sedentary behavior in a school setting and may be interpreted only as non-moving activities (stationary behavior).